(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Assessment of nutritional status and related factors in stroke patients with nasogastric tube feeding at the stroke center, Phu Tho province general hospital. Methods: Cross-sectional descriptive study. Results: Our study subjects were predominantly male, with a male-to-female ratio of 1.6:1. The age group 66–79 accounted for the highest proportion at 43.4%. At the time of hospital admission, the majority of patients (80%) had normal nutritional status (BMI: 18.5–24.9), while only 19.7% were malnourished (BMI < 18.5). The prevalence of malnutrition (BMI < 18.5) was highest in the ≥80 age group and showed an increase at discharge compared to admission (44.4% vs. 38.9%). Using the Subjective Global Assessment (SGA) method to evaluate nutritional status, the highest malnutrition rate was observed in the ≥80 age group. According to the SGA evaluation, 57.9% of patients with moderate malnutrition had a BMI < 18.5, while 60% of patients with severe malnutrition also had a BMI < 18.5. There was an association between malnutrition status at discharge (as assessed by SGA) and factors such as infection, mechanical ventilation, and diarrhea. No significant differences in nutritional status were observed between the two types of stroke. However, there was a relationship between the NIHSS clinical score and malnutrition status at discharge; patients with severe clinical admission (NIHSS ≥ 16) had an increased risk of malnutrition at discharge. Conclusion: Stroke patients receiving nasogastric tube feeding showed an increased rate of malnutrition compared to the time of hospital admission. The proportion of malnourished patients (BMI < 18.5) in the ≥80 age group was the highest at admission (38.9%) and further increased at discharge (44.4%). The rate of malnutrition based on SGA scores was higher in patients with the following conditions: mechanical ventilation; infections; diarrhea; and an NIHSS clinical score of ≥16 at the time of admission.